Deep brain stimulation for Parkinson’s disease - Okun, Michael S. (Henry Stewart Talks, 2014)
Deep Brain Stimulation, Mechanisms of action: What is the science and biology behind DBS, Screening for DBS: The use of an interdisciplinary team, Targets for DBS: The possible brain targets, Tailoring DBS: How to make personalized therapy, Evidence Base: Review of the recent randomized studies of DBS, Adverse events: The issues that may emerge with DBS, Horizon: What will future therapies look like